(untitled) (Future Cities and Environment, 2021)
Today, the building sector has a large share in global energy consumption. The building stock, which has increased with the increasing population, contributes more to this consumption day by day. School buildings, which constitute an important part of public buildings, are among the most used building types in the daily cycle and also have a high energy demand for heating, cooling and electricity loads. In Turkey, the implementation of the same type of school projects in different climate regions without considering the context and climatic conditions increases the amount of energy consumption. This study provides a framework for reducing energy loads in school buildings using passive design strategies. Located in two different climatic regions of Turkey, in Istanbul and Ankara, a primary school building is taken into consideration for comparison of type projects in the context of energy performance and single-objective optimization process to minimize energy use intensity (EUI). As a result of the optimization processes carried out depending on the parameters related to the building envelope, the energy performance for the Istanbul climate is improved by 5.05%, while this rate is 4.09% for the Ankara climate. The best solution individual parameters of both climate types have very close values to each other. It is thought that more efficient results can be obtained with the multi-objective optimization processes of the studies to be carried out to evaluate the type school projects on the basis of different climates.